CITREX 2024 UMPSA celebrates innovative researchers - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 9 May 2024 - The 14th edition of the Creation, Innovation, Technology & Research Exposition (CITREX) 2024 of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) saw a total of 93 gold winners, 126 silver winners and 35 bronze winners involving 255 entries from the categories of staff, IPT students and school students.